Management Compensation's Impact on Tax Avoidance in Indonesia With Moderation of Management - Arifianti, Novalina; Heni Agustina (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2025)
This study aims to determine the significance of management compensation on tax avoidance and the interaction between management compensation and management stock ownership on tax avoidance in the consumption industry 2020-2023. The method used is Multiple Regression Analysis (MRA) with moderation of management ownership. The results show that management compensation is significant in relation to tax avoidance. Meanwhile, the interaction between management compensation and management ownership is not significant in relation to tax avoidance. Percentage of management ownership is not large enough to change their decisions regarding tax strategies. So that companies do not have to add management shares in the compensation package to motivate management to take tax avoidance actions.